Asymmetric accumulative roll bonding of aluminium-titanium composite sheets - Hoi Pang Ng; Przybilla, Thomas; Schmidt, Christian; Lapovok, Rimma; Orlov, Dmitry; Höppel, Heinz Werner; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2013)
Aluminium–titanium (Al/Ti) composite sheets were fabricated via asymmetric accumulative roll bonding (AARB), which capitalises on additional shear to enhance plastic deformation. Multi-layers of Al alloy (AA1050) and commercially-pure Ti sheets were alternatively stacked and rolled-bonded with varied roll diameter ratios (dr) ranging from 1 to 2, for up to four passes. Annealing of selected composite sheets was subsequently carried out at 600 °C for 24 h to compare the rates of solid-state diffusion reactions between Al and Ti components. Mechanical tests revealed that both tensile strength and ductility of the sheets increase systematically with dr. The microstructures and the Al/Ti interfaces of the sheets were analysed in detail using TEM, SEM and FIB techniques. It is shown that not only does AARB lead to a more refined grain size of the Al matrix but also it promotes the development of a nanostructured surface layer on Ti that comprises crystallites of 50–100 nm in size, which is otherwise absent in the case of symmetric ARB (i.e. dr=1). The AARB-processed sheets exhibit a larger thickness of the interdiffusion layer at the Al/Ti interfaces than the counterparts processed via the symmetric ARB route, the difference being in excess of 15%. The effects and the implications of AARB processing on mechanical behaviour and diffusion kinetics are discussed with respect to the microstructural evolutions.
WW1::955